Pengaruh Expertise, Attractiveness, Trustworthiness, dan Review Quality Terhadap Purchase Intention Produk Kosmetik - Feni Nafisatun Malikhah; Dewi Noor Susanti (P4M STIE Putra Bangsa, 2021)
Purpose of this study was to determine the effect of expertise, attractiveness, trustworthiness, and review quality on purchase intention. The population in this study were all Putra Bangsa University students who had watched Rachel Goddard's Beauty Vlogger content. This study uses purposive sampling method with a sample of 100 respondents. Based on statistical methods, multiple linear regression tests were carried out, validity tests, reliability tests, classical assumption tests (multicollinearity test, heteroscedasticity test, and normality test), partial test, stimulus test and coefficient of determination test. Based on the results of the study, it can be seen that expertise has a simultaneous effect on purchase intention, attractiveness, trustworthiness, and review quality has a simultaneous effect on purchase intention of 35.7%. The results of this study indicate that based on the validity and reliability test all variables are declared valid and reliable. Based on the results of the t-test of expertise and trustworthiness, there is no significant effect on purchase intention, while attractiveness and review quality have a significant effect on purchase intention.